The Federal Democratic Republic of Ethiopia : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper argues that for Ethiopia to continue sustaining robust growth, leveraging the transformation power of the private sector, especially entrepreneurs, is essential. Although Ethiopia's public sector-led development strategy has delivered strong results over the past decade, it has been facing significant challenges in recent years. A model-based analysis of the country's investment program indicates that, despite positive long-run growth effects, transition challenges and macroeconomic trade-offs are associated with different financing strategies. Heavy reliance on domestic bank borrowing may require substantial fiscal and macroeconomic adjustments as well as entail a sharp increase in inflation. External commercial borrowing, on the other hand, may ease these adjustments but at the cost of significant increases in debt to gross domestic product ratios. Comparing Ethiopia's development experience-especially in terms of structural transformation and competitiveness-with that of selected Asian countries indicates differences which point to possible adjustments in Ethiopia's development approach.